Chronic Low-Dose Phoxim Exposure Impairs Silk Production in Bombyx mori L. (Lepidoptera: Bombycidae) by Disrupting Juvenile Hormone Signaling-Mediated Fibroin Synthesis - Xinyi Xie; Jiayin Hou; Meng Li; Zhiyu Liu; Mengai He; Chenxi Li; Xiaohua Du; Liezhong Chen (Toxics, 2025)
Phoxim is a pesticide extensively applied in mulberry fields, and residues may persist on leaves even after the recommended pre-harvest interval. However, the potential risks of these residues to Bombyx mori L. (Lepidoptera: Bombycidae) have long been overlooked. The results demonstrated that chronic low-dose exposure from the second to fifth instars significantly impaired silkworm development and silk production. Specifically, larvae in the 0.316 μg/mL treatment group (1/2 LC50) exhibited a significant reduction in body weight, while the cocoon shell ratio was significantly decreased in both the 0.079 μg/mL (1/8 LC50) and 1/2 LC50 groups. Cocoon deformities were observed in the 0.032 μg/mL (1/20 LC50), 1/8 LC50, and 1/2 LC50 groups. Histopathological analysis revealed silk gland damage in the treatment groups, with severity increasing with higher phoxim concentrations. Biochemical analyses indicated elevated malondialdehyde (MDA) levels accompanied by increased superoxide dismutase (SOD) and peroxidase (POD) activities. Notably, phoxim exposure selectively reduced juvenile hormone (JH) titers without affecting ecdysone titers. JH-regulated genes including the receptors Met1 and Met2, and transcription factors Kr-h1 and Dimm were downregulated, accompanied by suppressed expression of the fibroin synthesis gene Fib-H. These results collectively indicate that chronic low-concentration phoxim exposure disrupts endocrine regulation, damages silk gland integrity, and ultimately reduces silk production in silkworm.